Virtual microscopy: The future of pathological diagnostics, dental education, and telepathology - R M Vatchala Rani; B C Manjunath; Manas Bajpai; Rohit Sharma; Pooja Gupta; Akshay Bhargava (Wolters Kluwer Medknow Publications, 2021)
Objectives: The objectives of this study were as follows: (1) to provide an overview of the feasibility, utility, merits, and demerits of virtual microscopy (VM) in pathological diagnostics and (2) to evaluate its advantages in dental and medical teaching over conventional microscopes. Materials and Methods: A literature survey was carried out in August 2020 in electronic databases such as PubMed using keywords such as virtual microscopy and whole slide imaging. The searches revealed 956 articles out of which 36 were selected after reading the full-text articles. Results: The review of 36 articles revealed that VM or whole-slide imaging (WSI) allows access to entire scanned sections of tissue that can be viewed on a computer in exactly the same way as conventional glass slides with a microscope and can be explored at several magnifications. VM offers many advantages like ease of accessibility through the Internet anytime or in any place, and moreover, the virtual slide does not get damaged or fade away like glass slide. Since it increases learning and comprehension, virtual microscopes have been used extensively in dental and medical education. Conclusions: VM opens a new world in tissue-based diagnosis through digitization of slides. The experiences of telepathology applications have already proved that it is a promising technology which has been adopted by histopathologists and cytologists across the world and contributing immensely to telepathology consultation in underserved areas. It is a feasible, valid, and approved technology for pathological diagnosis.